OCCURRENCE OF NON -TUBERCULOUS MYCOBACTERIA IN ENVIRONMENTAL SAMPLES AT PILGRIMAGE SITES - B.S.M.RONALD; P.KAVITHA RANI (International Journal of Pharma and Bio Sciences, 2013)
Non-tuberculous mycobacteria (NTM) inhabit a wide variety of environmental including different water bodies, soil, aerosol, animals and humans. NTM are also known as environmental mycobacteria which can cause mycobacteriosis .Humans, animals and fresh water fauna are exposed to mycobacteria in water. HIV seronegative and immunocomprised patients are most vulnerable to acquire this opportunistic infection. The objective of this study was to identify and characterize the non tuberculous mycobacteria from soil & water bodies near pilgrimage spots where humans have increased access. The mycobacterial isolates were identified using phenotypic methods and 16S rRNA PCR and sequencing of hyper variable region which was proved to be less time consuming and cost effective method. In conclusion, the present study revealed the presence of NTM (32%) viz. M.intracellularae, M.shimoidei, M.terrae, M.aichense M.woliniski and M.fortuitum in the water samples collected from pilgrimage sites which can be potential pathogens.